Corrosion and Biocompatibility of Pure Zn with a Micro-Arc-Oxidized Layer Coated with Calcium Phosphate - Yixuan Shi (MDPI AG, 2021)
Recent studies have indicated a great demand to optimize the biocompatibility properties of pure Zn as an implant material. For this purpose, CaZn2(PO4)2·2H2O (CaZnP) was prepared using hydrothermal treatment (HT) combined with micro-arc oxidation (MAO) on pure Zn substrate to generate biodegradable implants. The polarization test and electrochemical impedance spectroscopy indicated that the MAO1−HT coating could modulate the corrosion behavior of MAO1 by filling the crevice between the coating and the substrate. Immersion test evaluation revealed that the osteogenic properties of MAO1−HT coating were better than that of pure Zn substrate, as evidenced by the molar ratio of Ca and P, which increased after soaking in simulated body fluid (SBF) for up to 10 days. In addition, L-929 cells cultured in the 100%, 50%, and 25% extracts of MAO1−HT coated samples exhibited excellent cytocompatibility. Meanwhile, cell adhesion was promoted on the surface with high roughness generated during MAO and HT processes. In summary, the calcified coatings improved biocompatibility and adjusted the degradation rates of pure Zn, broadening the application of Zn alloys.